2012
DOI: 10.2753/jei0021-3624460227
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Risk in Japan: Consumers' Risk Mitigation Responses After the Great East Japan Earthquake

Abstract: Abstr actThe Great East Japan Earthquake and subsequent tsunami on March 11 were a reminder of Japan's huge earthquake risk and need for preparedness. The northeastern part of the country witnessed devastating human suffering and physical damage. The destructive impact of the earthquake has enhanced consumer's earthquake preparedness even in unaffected areas. This paper uses unique survey data collected after the earthquake to study how consumers reacted to this catastrophic event. We find that self-reported, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
(3 reference statements)
1
11
0
Order By: Relevance
“…In another study, which was conducted in Alabama in the United States, McCormick et al (2013) found that individuals whose annual income fell below $25,000 were less prepared for an emergency than individuals who had a higher income. Similar findings were echoed in a study conducted in Japan following the 2011 Sendai earthquake and subsequent tsunami (Naoi et al, 2012).…”
Section: Factors Affecting Individual Disaster Preparednesssupporting
confidence: 76%
See 1 more Smart Citation
“…In another study, which was conducted in Alabama in the United States, McCormick et al (2013) found that individuals whose annual income fell below $25,000 were less prepared for an emergency than individuals who had a higher income. Similar findings were echoed in a study conducted in Japan following the 2011 Sendai earthquake and subsequent tsunami (Naoi et al, 2012).…”
Section: Factors Affecting Individual Disaster Preparednesssupporting
confidence: 76%
“…Studies have consistently shown an association between socioeconomic status and disaster preparedness in the United States 2014McCormick, Pevear, & Xie, 2013;Russell et al, 1995) and international samples (Naoi, Seko, & Ishino, 2012;Tekeli-Yesil et al, 2010). A study conducted in Turkey (Tekeli-Yesil et al, 2010) showed correlations between income and education and predisaster preparedness: Individuals with better economic security and high educational attainment tend to be more prepared in times of an emergency event.…”
Section: Factors Affecting Individual Disaster Preparednessmentioning
confidence: 99%
“…We also mention two survey-data studies on how risk preferences of households have changed after the Tohoku earthquake (the Great East Japan earthquake) in 2011. Naoi et al (2012) find that although respondents seemed to be more prepared for natural disasters after the Tohoku experience, actual (costly) mitigation activities depend on household income. Hanaoka et al (2015) examine whether risk preferences of men and women have changed, and if so whether they changed in a different way, after the Tohoku earthquake.…”
Section: Introductionmentioning
confidence: 87%
“…Those in neighboring areas who were not directly affected also are more likely to prepare. In an analysis of the aftermath of the 2011 earthquake and subsequent tsunami in Japan, self-reported preparedness for natural disaster increased (Naoi et al, 2012). Specifically, 60 percent of respondents to a survey reported that they were better prepared at the time of the survey than they were before the disaster.…”
Section: Preparation For Natural Disastersmentioning
confidence: 99%